A Framework for a European Economic Recovery After COVID-19 - Julia Anderson; Simone Tagliapietra; Guntram B. Wolff (Intereconomics, 2020)
The success of support measures as COVID-19 lockdowns are relaxed depends on the type of recovery the EU wants to achieve.
Keywords: 330